PERATAAN LABA DAN PENGARUHNYA TERHADAP RETURN SAHAM - Hendra Agustinus Marbun (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2017)
This study aims to examine the influence of profitability, debt, dividend and company size factors on the company practice of income smoothing and to test whether there is a difference of stock returns between profit companies with non-profit smoothing. The object of this research is a public company on BEI listed as group Liquid 45 (LQ45). This study used logistic regression and difference test statistic model to test the difference between the profit smoothing and not the revenue smoothing of stock returns. The conclusions in this study: Profitability, debt, dividend, and firm size factors do not significantly affect earnings smoothing. And, there is no significant difference between stock returns between the income smoothing actors and non-income smoothing actors. The results of this study are consistent with research conducted by Juniarti and Carolina (2007), Li Jung Tseng and Chien Wan Lai (2007), and Zulfa and Anugerah (2007)